Persuasi Rute Periferal Exo Sebagai Brand Ambassador Scarlett Whitening Terhadap Impulsive Buying - Maretha, Grace; Pamungkas, Indra Novianto Adibayu; Pramesthi, Jasmine Alya (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The popularity of K-Wave amongst Indonesian creates a competition for brands, resulting them competing to use Korean artists as brand ambassadors. This practice is widely adopted in business, particularly in the beauty industry, which is rapidly growing in Indonesia. This research aims to determine the effect of EXO's peripheral route persuasion as the brand ambassador of Scarlett Whitening on impulsive buying behavior. The study uses a quantitative approach to provide detailed statistical analysis on the influence of brand ambassadors on consumer impulsive buying. Data collected through an online questionnaire, distributed to 385 respondents who met the requirements of sample criteria. The results of the study indicate a significant positive influence of peripheral route persuasion on impulsive buying behavior. This means that the presence of EXO as a brand ambassador is effective in delivering marketing messages through the peripheral route, which includes elements such as likability and attractiveness, driving consumers to make impulsive purchases.